PERALIHAN HAK WARIS MENJADI WASIAT WAJIBAH KEPADA AHLI WARIS MURTAD - Muriani R, Karina Novian; Maulana, Arif; Indana, Della Octavia; Rosadi, Aden; Yuniarti, Sri (Program Studi Hukum Keluarga Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
One of the conditions for someone to receive inheritance is that one of the family members dies (muwaris) and leaves behind his/her assets. Then the heirs can obtain a portion of the inheritance in accordance with the applicable provisions (faraid). However, things are different if one of the heirs is of a different religion or converts from Islam to a religion other than Islam (apostatizes), then according to Islamic jurisprudence scholars, he is no longer an heir and absolutely does not receive a share of the inheritance of the muwaris. This article uses a qualitative descriptive method with data collection techniques in the form of literature. This article is interesting to discuss in more depth because if an heir has apostatized, he will not receive a single cent of inheritance from the muwaris because Islamic law states that a Muslim cannot inherit from a non-Muslim. This is also clearly regulated in the Compilation of Islamic Law (KHI). However, there is another option if an heir who was previously Muslim becomes an apostate, but he still wants to get a share of the inheritance, Therefore, Islamic law in Indonesia permits it by way of a mandatory will, on the condition that the gift of assets does not exceed 1/3.